Improving the spacer-concrete interface for bond strength and durability - Muslim,F; Wong,HS; Buenfeld,NR (2018)
Spacers are important devices in reinforced concrete that are used to support reinforcing steel during concreting in order to achieve the required concrete cover. They are placed at every meter length or less of steel reinforcement and left permanently in the structure. However, it has been shown that the interface between spacer and concrete is highly porous and microcracked. This lowers the resistance of the concrete cover to the ingress of aggressive agents causing degradation. This study aims to address this problem by improving spacer design to enhance bond strength and durability of the spacer-concrete interface. Cementitious spacers with a range of surface textures were produced prior to casting into concrete. Samples were prepared with CEM I Portland cement at a water/cement (w/c) ratio of 0.4 and cured for 1, 7, and 28 days in a fog room and then conditioned at 50°C to equilibrium moisture content. The spacer-concrete interface was then tested for tensile bond strength and mass transport properties including oxygen diffusivity, oxygen permeability, and water absorption. The measured surface properties were correlated to the measured bond strength and transport properties to establish the effects of surface texture on the spacer-concrete interface.